RETRACTED: Towards Sustainable Environment in G7 Nations: The Role of Renewable Energy Consumption, Eco-innovation and Trade Openness - Olanrewaju, Victoria Olushola; Irfan, Muhammad; Altuntaş, Mehmet; Agyekum, Ephraim Bonah; Kamel, Salah; El-Naggar, Mohamed F. (Frontiers in Environmental Science, 2022)
Some of the globe's most economically advanced nations make up the G7. Nevertheless, in tandem with such strong economic growth, the environmental conditions in these nations have deteriorated, raising serious issues among stakeholders. Therefore, we examines the effect of eco-innovation and trade openness on CO2 emissions in G7 nations. We also take into account the role of renewable energy, economic growth and nonrenewable energy use using dataset covering the period from 1990-2019. We employed recent econometric techniques such as SH and CSD, Westerlund cointegration, FMOLS, DOLS, panel quantile regression and panel causality tests to assess these associations. The outcomes of the CSD and SH tests disclosed that using first-generation unit root test will produce bias outcomes. Furthermore, the outcomes of the Westerlund cointegration disclosed support long-run association between CO2 and its drivers. In addition, the results of the long-run estimators (FMOLS and DOLS) unveiled that nonrenewable energy and trade openness contribute to the damage of the environment while economic expansion, renewable energy and eco-innovation enhance the quality of the environment. Furthermore, the outcomes of GDP, REC and ECO curb CO2 while NREC energy and TO surge CO2. Finally, the outcomes of the panel causality test unveiled that CO2 emissions can be predicted by all the exogenous variables.